Effect of Cellulase Supplementation on in vitro Digestibility and Energy, Crude Fiber and Cellulose Content of Sago Palm (Metroxylon sp.) Waste as Broiler Chicken Feed - Zulkarnain, Deki; Zuprizal; Wihandoyo; Supadmo (Pakistan Journal of Nutrition, 2016)
Objective: The purpose of this study is to determine the amount of cellulase enzyme needed to optimize sago palm waste feed digestibility in vitro . This information can provide the basis for use of sago palm waste in broiler chicken feed. Methodology: Cellulase was added to the sago palm waste feed material at 5 different concentrations and five trials were conducted for each feed mixture. The parameters measured in this study were: in vitro dry matter digestibility (IVDMD), in vitro organic matter digestibility (IVOMD) and in vitro crude protein digestibility (IVCPD). The metabolic energy, crude fiber and cellulose contents in sago palm waste were also determined. The resulting data were analyzed statistically with a directional completely randomized design. Results: Sago palm waste with cellulase added to 0.75 g cellulase kg–1 waste had the best IVDMD (35.94 vs 19.32% for 0 g cellulase) and IVOMD (35.25 vs 19.32% for 0 g cellulase) values. Optimal values for the crude fiber and cellulose content were also seen for 0.75 g cellulase kg–1 waste with a maximum reduction to 12.79% crude fiber content (decreased by 23.69% compared to untreated waste) and 7.91% cellulose content (decreased by 29.56% relative to untreated waste). The crude protein digestibility and sago palm waste metabolic energy content at various cellulase concentrations were similar but 0.75 g cellulose kg–1 sago palm waste produced optimal crude protein digestibility and metabolism content. Conclusion: Addition of cellulase enzyme to sago palm waste at 0.75 g cellulose kg–1 sago palm waste improves IVDMD and IVOMD. This amount of cellulase also produced the best crude fiber and cellulose contents. Together these results suggest that cellulase can be used to improve the qualities of sago palm waste as a feed for broiler chickens.